Report of The Prices Sub-Committee of the Policy Committee on Agriculture, Forestry and Fisheries - Planning Commission (Planning Commission, 1944)
It is necessary to raise the standard of living of the agriculturist and the agricultural labourer to the highest possible level by taking immediate steps : (i) to increase agricultural production to the maximum extent possible and (ii) to improve agricultural efficiency in all directions.
Planning Commission Government of India
Planning Commission Government of India